TEXT AND CONTEXT OF NEWSPAPER OPINION RUBRIC AND ITS UTILIZATION AS TEACHING MATERIALS IN SENIOR HIGH SCHOOL - Kusumaningrum, Yulia; Tuan, Nguyen Thanh; Zulianto, Sugit; Mulyono, Slamet (Basastra: Jurnal Bahasa, Sastra, dan Pengajarannya, 2022)
This study aims to describe and explain: (1) aspects of the textual discourse of the opinion rubric in the Solopos newspaper, (2) the contextual aspects of the opinion rubric in the Solopos newspaper, and (3) the relevance of the textual and contextual aspects of the opinion rubric in the newspaper. Solopos news with teaching materials in high school. This study uses a qualitative descriptive research design with a content analysis approach. The data in this study are in the form of words, phrases, and sentences. The data sources used in this study are documents, namely the opinion rubric of the Solopos newspaper January-February 2021 edition, and the informants are Indonesian language teachers in class XII SMA, opinion writers, and opinion editors for the Solopos newspaper. Data collection techniques used, namely document analysis and interviews. Test the validity of the data using theoretical triangulation and data source triangulation. The data analysis technique used is the agih method. The results of this study indicate that: (1) textual aspects that support the integrity and cohesion of opinion discourse consist of grammatical cohesion and lexical cohesion; (2) contextual aspects of opinion discourse can be understood using the principle of personal interpretation, the principle of locational interpretation, and the principle of temporal interpretation; and (4) the opinion rubric for the January-February 2021 edition of the Solopos newspaper can be used as an alternative material for teaching editorial texts for class XII SMA.